If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24=-7+9(h-4)
We move all terms to the left:
24-(-7+9(h-4))=0
We calculate terms in parentheses: -(-7+9(h-4)), so:We get rid of parentheses
-7+9(h-4)
determiningTheFunctionDomain 9(h-4)-7
We multiply parentheses
9h-36-7
We add all the numbers together, and all the variables
9h-43
Back to the equation:
-(9h-43)
-9h+43+24=0
We add all the numbers together, and all the variables
-9h+67=0
We move all terms containing h to the left, all other terms to the right
-9h=-67
h=-67/-9
h=7+4/9
| 3w+-2=7 | | 8+3n-7=9n+4-5n | | 34c-6=2 | | 24=5z+3z-8 | | 8-x-3=0 | | 4−r=–2r | | 4(x+1)+2x=22 | | 4(-2-9.2x=3(2-7.6x) | | 8x+4x-3x=7-4 | | x+3/8=7/6 | | 200m-75m+63,050=65,650-200m | | -14d-12+19d=15+2d | | 5x-2(4x+3)=18 | | -10-7x+x=8 | | -21-4x=-5-4(4-6x) | | 9x+9=2x-27 | | 16.5-4.5a=-5(7.5a-2) | | 2(r-1)=4 | | -22=a-17 | | -9+-2j=1 | | z+5=4+5 | | 5(x-3)^2/3=80 | | 2/5x-14=50 | | -5.2x(x-2.25)=15.6 | | 8x-2x-1=53 | | 4+x/(-9)=6 | | 8a-6=+a-1 | | -8p+3=-7p-2 | | 5(v+1)=-3v+13 | | 4m/14=12 | | 3(-5h-4)=2(h-6) | | -1.2y-4.2y=-3.87 |